Implikasi Postmodernisme Dalam Masyarakat Kontemporer (Analisis Paradigma Pemikiran Tokoh Jean Francois Lyotard) - Erlina, Erlina; Helmi Syaifuddin (UIN Sunan Kalijaga Yogyakarta, 2023)
This article aims to investigate the implications of postmodernism in contemporary society by analyzing the paradigm of thought of the figure Jean-François Lyotard. Lyotard is known as one of the leading thinkers in postmodern thought, and this research aims to understand how his idea of skepticism towards grand narratives influences and permeates the structures of power, knowledge, and language in the context of contemporary society. This study uses a qualitative approach with a focus on the analysis of key texts by Jean-François Lyotard, especially